Evaluation of Energy-Economy-Environment System Coordination in Southwest China under the Perspective of Carbon Neutrality and Its Influencing Factors Research - Liu, Huiyue; Sun, Xiaowen (International Journal of Global Economics and Management, 2025)
Driven by the "carbon neutrality" policy, the coordinated development of energy, economy and environment has become an important part of sustainable development. In this paper, four provinces and cities in southwest China, including Yunnan, Guizhou, Sichuan, and Chongqing from 2011 to 2021, were taken as the research objects, and the coupling coordination model was used to construct a comprehensive evaluation index system of energy, economy, and environment, and the coupling coordination level of the three systems was empirically analyzed, and the influencing factors were analyzed. The final results show that the coordinated development level of energy-economy-environment system in the four provinces is greater than 0.5 in 2021, which has entered the coordination stage, but there is still a distance from high-quality coordination. Based on this, this paper puts forward policy suggestions to promote the coordinated development of energy, economy and environment in four provinces in southwest China.